Application of digital orthopedic technology in orthopedic clinical teaching - Xiao-Dong XU; Fu-Qiang GAO; Ying CHEN; Peng LIN; Wei SUN (Yixue xinzhi zazhi)
Application of digital orthopedic technology plays a critical part in orthopedic clinical teaching. There are many disadvantages to traditional teaching methods and media. However, the rapid development of digital technology in orthopedics combined with computer, image processing, 3D printing and other new medical processing methods, has the advantages of visualization, visibility, repeatability and operability which has a broad potential application in clinical teaching.